Ganglioside GM3 deficiency enhances mast cell sensitivity - Komuro, Mariko; Mizugaki, Hinano; Nagane, Masaki; Morimoto, Misako; Fukuyama, Tomoki; Ogihara, Kikumi; Naya, Yuko; Yokomori, Emi; Kaneshima, Kimika; Kawakami, Yasushi; Kamiie, Junichi; Shibata, Yuki; et al. (The FEBS journal, 2023)
Mast cells are a significant source of cytokines and chemokines that play a role in pathological processes. Gangliosides, which are complex lipids with a sugar chain, are present in all eukaryotic cell membranes and comprise lipid rafts. Ganglioside GM3, the first ganglioside in the synthetic pathway, is a common precursor of the specifying derivatives and is well known for its various functions in biosystems. Mast cells contain high levels of gangliosides; however, the involvement of GM3 in mast cell sensitivity is unclear. Therefore, in this study, we elucidated the role of ganglioside GM3 in mast cells and skin inflammation. GM3 synthase (GM3S)‐deficient mast cells showed cytosolic granule topological changes and hyperactivation upon IgE‐DNP stimulation without affecting proliferation and differentiation. Additionally, inflammatory cytokine levels increased in GM3S‐deficient bone marrow–derived mast cells (BMMC). Furthermore, GM3S‐KO mice and GM3S‐KO BMMC transplantation showed increased skin allergic reactions. Besides mast cell hypersensitivity caused by GM3S deficiency, membrane integrity decreased and GM3 supplementation rescued this loss of membrane integrity. Additionally, GM3S deficiency increased the phosphorylation of p38 mitogen‐activated protein kinase. These results suggest that GM3 increases membrane integrity, leading to the suppression of the p38 signalling pathway in BMMC and contributing to skin allergic reaction.